Pemanfaatan Media Tiktok Sebagai Media Pembelajaran Pendidikan Agama Islam - Safriyandi Barus; Jamaluddin Sufri Situmorang; Muhammad Rido; Hasrian Rudi (STIKes Ibnu Sina Ajibarang, 2024)
The development of TikTok social media is in line with the current digital era. This gives rise to social media which can be a learning medium because social media really attracts attention and is close to the millennial generation who are attached to the digital world. One of the social media that is currently popular is the TikTok application. TikTok can be an interesting and fun learning medium. The use of the TikTok application as a learning medium is expected to help students and educators in learning. Therefore, this research aims to show that TikTok social media can be an alternative and interactive learning media in pai learning. The method used is a qualitative case study approach and literature study by analyzing several articles that are relevant to the development of TikTok as a learning medium. The results of the study show that the use of TikTok social media as a learning medium can increase students' activeness and creativity in the learning process. Students can freely express their creativity through TikTok with a variety of features, thus making TikTok an effective learning medium in creating interactive pie learning. This research has the effect of making TikTok social media an interactive learning medium for educators and students in pai learning.